PENGELOLAAN FASILITAS OBJEK WISATA AIR TERJUN TEMBULUN KINUTAN KECAMATAN SEBERIDA KABUPATEN INDRAGIRI HULU - Hutabarat, Oki Prawati BR; Yulia, Nur Arini (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2025)
This research discusses the management of facilities at the Tembulun Kinutan Waterfall tourist attraction located in Seberida District, Indragiri Hulu Regency. The research aims to determine how the tourism facility management process is carried out, and to identify the factors that cause management to be less than optimal. The research method used is descriptive qualitative with data collection techniques including observation, interviews, and documentation. The research findings indicate that the facility is managed independently by the owners and employes, without direct involvement from the local government. Available facilities include gazebos, prayer rooms, toilets, changing rooms, parking areas, photo spots, food stalls, and tent and float rentals. However, some facilities are damaged and not fully utilized, such as damaged gazebos, inadequate toilets and changing rooms, and food stalls that are rarely open. The main factors hindering management are budget limitations, a shortage of professional staff, a lack of visitor awareness regarding cleanliness, and the absence of full government support. Nevertheless, the management is working to carry out routine maintenance, repair damaged facilities, and keep the area clean. This research is expected to contribute to managers, local governments, and academics as a basis for consideration in the development of regional tourism. Keywords : Management, Tourism Facilities, Waterfall, Tembulun Kinutan, Indragiri Hulu